Child Participatory Action Research as a Failed Emancipatory Project - Garlen, Julie; Hembruff, Sarah; Ruddy, Evie Johnny (The Canadian Journal of Action Research, 2026)
In this article, we discuss the results of our efforts to collaboratively engage in participatory action research with children ages 10-11. Despite our best efforts to be intentional about breaking down the adult-child binary to create space for the child participants to act as co-researchers, in reflecting on the results of the project, we ultimately determined we did not achieve our intended emancipatory aim. Here, we describe the lessons we took away from this project and how they might inform future practices for working with children, as researchers, teachers, and advocates.